STRATEGI GURU PAI DALAM MENGATASI PERBEDAAN KOMUNIKASI ANTAR BUDAYA SISWA KELAS XI DI SMKN 1 JAKARTA - Tri Saputra; Tajriyah Tajriyah; Kamal Bagus Hutomo; Siti Nadiatul Hasanah (JIP: Jurnal Ilmu Pendidikan, 2025)
Cultural differences in schools can affect student interaction, especially in learning activities, which has the potential to cause misunderstandings. This study aims to describe the strategies applied by PAI teachers in overcoming differences in intercultural communication among grade XI students of SMKN 1 Jakarta. Methods This research uses Mix Methods. Qualitative approach with a focus on data collection through direct observation, interviews, and document analysis. The method also uses a quantitative approach and field research using the Google Forms platform to take student responses. The findings were then processed using Likert scale calculations using SPSS. Based on the results of the data analysis of the paired samples t-test, it is known that there is a significant difference between variable X (PAI teacher strategy) and variable Y (differences in intercultural communication). It can be seen from the significance value (2-tailed) of 0.00<0.05 which means that there is a significant influence of the treatment of variable X (PAI teacher strategy) on variable Y (differences in intercultural communication), which can be interpreted that the PAI teacher's strategy in overcoming differences in intercultural communication is declared effective.